2005
DOI: 10.1536/ihj.46.631
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Anticardiolipin Antibodies and Recurrent Cardiac Events in Patients With Acute Coronary Syndrome

Abstract: SUMMARYTo determine whether the presence of anticardiolipin (aCL) antibodies in patients with acute coronary syndome is predictive of recurrent cardiac events in hospital stay and follow-up.The study population consisted of 80 patients with acute coronary syndrome. IgM and IgG aCL levels were determined before hospital discharge. We divided the patients into those with an aCL IgG ≥ 40 IgG phospholipid units (group I, n = 30) and those with an aCL IgG < 40 IgG phospholipid units (group II, n = 50). All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…A strong association between the levels of aCL antibodies and the outcomes of PCI after an ACS has also been observed. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A strong association between the levels of aCL antibodies and the outcomes of PCI after an ACS has also been observed. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, ACLA promote AT by attracting monocytes into the vessel wall and inducing monocyte adherence to endothelial cells. All of this is mediated by adhesion molecules such as ICAM-1, VCAM-1, and E-selectin [7, 92]. The APLA should be considered more than an AT marker since they can enhance AT and are proatherogenic [93, 94].…”
Section: Discussionmentioning
confidence: 99%
“…Gürlek et al [18] reported a strong association between the levels of anticardiolipin antibodies and the outcome of PCI after an ACS. In this study, higher levels of anticardiolipin antibodies predicted increased rates of restenosis after PCI, without an effect on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is a paucity of data regarding the outcome of patients with APS who undergo coronary revascularization. Small studies have demonstrated that patients with APS are predisposed to high rates of restenosis of the coronary arteries and vascular grafts after percutaneous coronary intervention (PCI) or coronary artery bypass graft surgery, respectively, causing significant morbidity and mortality [16,17,18,19]. Some of these studies were conducted more than a decade ago, in the percutaneous transluminal coronary angioplasty era, and are therefore less relevant for contemporary PCI practice [16,19].…”
Section: Introductionmentioning
confidence: 99%